CONTRIBUTION OF ECONOMIC SECTORS BASED ON BUSINESS FIELDS TO INDONESIA'S GDP GROWTH 2014-2023 - Azis R, Abdul; M, Wisra; Anisa, Nur (Management and Leadership Study Programme, 2025)
This study aims to analyze the contribution of economic sectors to Indonesia's GDP based on business fields during the administration of President Joko Widodo, using data from the Central Statistics Agency (BPS) and Bank Indonesia (BI) for the period 2014–2023. The method used is quantitative descriptive, which describes the contribution of each sector to GDP with a descriptive statistical approach and data visualization using graphs. The results of the study show that the manufacturing industry sector makes the largest contribution to GDP, followed by the trade and agriculture sectors. Sectors such as health services and education show significant fluctuations, while the construction and transportation sectors experience a stable growth trend. These findings provide a comprehensive picture of the dynamics of economic sectors and can be used as a basis for more effective economic policies in achieving national economic stability and sustainability.